An International Discourse Community, an Internationalist Perspective: Reading EATAW Conference Programs, 2001-2011 - Kearns, Judith; Turner, Brian (Journal of Academic Writing, 2015)
This article seeks to characterize the discourse community represented by the biennial conferences of the European Association for the Teaching of Academic Writing (EATAW). Drawing on information from EATAW’s conference programs, the authors define the topical emphases of the 565 standard presentation abstracts (SPAs) accepted for the first six conferences, identify some of the community’s dominant research practices and common methods of presentation, and track the changing international distribution of presenters over time. We conclude that the EATAW discourse community, true to its name, has remained focused primarily on pedagogy and on pragmatic research aimed at improving teaching practices. Working in a multilingual context, EATAW teachers/researchers tend towards an ’internationalist perspective’ (Horner and Trimbur 2002: 624), one that is attentive to linguistic and cultural differences and favours empirical research as a means of identifying diverse student needs. This perspective, along with a tendency toward cross-institutional and international research partnerships, stands in contrast to the perspective of the Conference on College Composition and Communication (CCCC) the conference which best represents the American composition tradition.